We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
373
1
avatar

f(x)=4x+7 and g(x)=3x-5.find (fog)(-4)

 Jul 1, 2017

Best Answer 

 #1
avatar+8207 
+3

\((f\circ g)(-4)=f(\,g(-4)\,)\)

 

f(x)  =  4x + 7                             Replace every instance of   x   with   g(-4)   .

f( g(-4) )  =  4( g(-4) ) + 7

 

 

And.....

g(x)  =  3x - 5                             Replace every instance of   x   with   -4   .

g(-4)  =  3(-4) - 5                        Simplify.

g(-4)  =  -17

 

f( g(-4) )  =  4( g(-4) ) + 7             On the right side, replace   g(-4)   with   -17

f( g(-4) )  =  4( -17 ) + 7               Simplify.

f( g(-4) )  =  -61

 Jul 1, 2017
 #1
avatar+8207 
+3
Best Answer

\((f\circ g)(-4)=f(\,g(-4)\,)\)

 

f(x)  =  4x + 7                             Replace every instance of   x   with   g(-4)   .

f( g(-4) )  =  4( g(-4) ) + 7

 

 

And.....

g(x)  =  3x - 5                             Replace every instance of   x   with   -4   .

g(-4)  =  3(-4) - 5                        Simplify.

g(-4)  =  -17

 

f( g(-4) )  =  4( g(-4) ) + 7             On the right side, replace   g(-4)   with   -17

f( g(-4) )  =  4( -17 ) + 7               Simplify.

f( g(-4) )  =  -61

hectictar Jul 1, 2017

18 Online Users

avatar
avatar